1991
DOI: 10.1097/00004032-199101000-00001
|View full text |Cite
|
Sign up to set email alerts
|

The Radiological Accident in Goiania

Abstract: The removal of a 50.9-TBq 137Cs source from a radiation therapy facility in Goiânia gave rise to a radiological accident in September 1987 whose proportions were aggravated by the 16-d interval from the beginning of a series of acts that resulted in the contamination of people and areas, to the moment of identification and seeking of aid. Data gathered from the declarations of persons involved in the accident, matched with the medical assessment and radiation monitoring of areas affected, made it possible to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…There is extensive evidence that widespread hemorrhages occurred in the Hiroshima and Nagasaki atomic bomb casualties, even in the relatively low radiation dose groups (311), with the estimated LD 50 values of approximately 2.5 (312, 313). Other information about hemorrhaging in humans after irradiation comes from accidental exposures in Norway (314) and Brazil (315, 316) in which several people were accidently exposed to whole body irradiation at doses near the human LD 50 and widespread hemorrhages were observed.…”
Section: Discussionmentioning
confidence: 99%
“…There is extensive evidence that widespread hemorrhages occurred in the Hiroshima and Nagasaki atomic bomb casualties, even in the relatively low radiation dose groups (311), with the estimated LD 50 values of approximately 2.5 (312, 313). Other information about hemorrhaging in humans after irradiation comes from accidental exposures in Norway (314) and Brazil (315, 316) in which several people were accidently exposed to whole body irradiation at doses near the human LD 50 and widespread hemorrhages were observed.…”
Section: Discussionmentioning
confidence: 99%
“…As the source was in powder form, the contamination spread rapidly. Some of the people who had been exposed were hospitalized with symptoms of acute radiation syndrome (ARS), such as vomiting and diarrhea, but as the cause of their illness was then unknown, they were treated as having a tropical disease or an allergic reaction ( IAEA, 1988 ; Rozenthal et al, 1991 ). On September 28, one of the patients connected her illness with the source and took part of the source in a bag to the public health department, this led to the discovery of the accident: A physician who suspected the illness could be ARS asked a physicist for help, they confirmed that the material in the bag was radioactive and the dose rate measured at surface was 10 Sv h −1 .…”
Section: Large-scale Radiological or Nuclear Incidentsmentioning
confidence: 99%
“…On September 28, one of the patients connected her illness with the source and took part of the source in a bag to the public health department, this led to the discovery of the accident: A physician who suspected the illness could be ARS asked a physicist for help, they confirmed that the material in the bag was radioactive and the dose rate measured at surface was 10 Sv h −1 . The physicist evacuated the area and notified the Brazilian National Nuclear Energy Commission (CNEN) immediately ( Rozenthal et al, 1991 ; Brandão-Mello, 1991 ).…”
Section: Large-scale Radiological or Nuclear Incidentsmentioning
confidence: 99%
See 2 more Smart Citations